Mold Alkaloid Cytochalasin D Modifies the Morphology and Secretion of fMLP-, LPS-, or PMA-Stimulated Neutrophils upon Adhesion to Fibronectin - Svetlana I. Galkina; Natalia V. Fedorova; Marina V. Serebryakova; Evgenii A. Arifulin; Vladimir I. Stadnichuk; Ludmila A. Baratova; Galina F. Sud'ina (Hindawi Limited, 2017)
Neutrophils play an essential role in innate immunity due to their ability to migrate into infected tissues and kill microbes with bactericides located in their secretory granules. Neutrophil transmigration and degranulation are tightly regulated by actin cytoskeleton. Invading pathogens produce alkaloids that cause the depolymerization of actin, such as the mold alkaloid cytochalasin D. We studied the effect of cytochalasin D on the morphology and secretion of fMLP-, LPS-, or PMA-stimulated human neutrophils upon adhesion to fibronectin. Electron microscopy showed that the morphology of the neutrophils adherent to fibronectin in the presence of various stimuli differed. But in the presence of cytochalasin D, all stimulated neutrophils exhibited a uniform nonspread shape and developed thread-like membrane tubulovesicular extensions (cytonemes) measuring 200 nm in diameter. Simultaneous detection of neutrophil secretory products by mass spectrometry showed that all tested stimuli caused the secretion of MMP-9, a key enzyme in the neutrophil migration. Cytochalasin D impaired the MMP-9 secretion but initiated the release of cathepsin G and other granular bactericides, proinflammatory agents. The release of bactericides apparently occurs through the formation, shedding, and lysis of cytonemes. The production of alkaloids which modify neutrophil responses to stimulation via actin depolymerization may be part of the strategy of pathogen invasion.